Luminescent Properties and Optical Amplification of Erbium‐Doped Nano‐Engineered Scandium‐Phospho‐Yttria‐Alumina‐Silica Glass Based Optical Fiber. Issue 7 (31st January 2018) - Reddy, Pinninty Harshavardhan; Das, Shyamal; Dutta, Debjit; Dhar, Anirban; Kir'yanov, Alexander V.; Pal, Mrinmay; Bhadra, Shyamal Kumar; Paul, Mukul Chandra
Abstract : In this work, a new erbium (Er) doped nano‐engineered scandium‐phospho‐yttria‐alumina‐silica (SPYAS) glass‐based optical fiber is reported, fabricated through the MCVD process, and solution doping technique, followed by a suitable thermal annealing of pristine preform. The fabrication process comprises the incorporation of erbium doped phase‐separated scandium‐yttria rich crystalline nanoparticles into the core region through in situ process based on phase‐separation and crystal growth phenomena. The material characterization results, obtained from transmission electron microscopy, electron diffraction pattern, energy dispersive X‐ray, electron probe micro analysis, and X‐ray fluorescence, confirm the formation of Er2 O3 doped crystalline phase‐separated scandium‐yttria rich nanoparticles in the core region. The formation of scandium‐ultra rich nano‐crystalline environment, possessing low photon energy around the erbium ions, enhanced the fluorescence intensity. Such kind of nano‐engineered glass reduces the noise figure around 4.35 dB, and provides broadband optical flat gain with an average value of 38.675 dB, varied by less than ±0. 7 dB spanning over a broad wavelength region of 1530–1590 nm compared to the pristine and Sc free Er‐doped fibers. Such kind of nano‐engineered glass based Er doped fiber will be useful for making highly efficient optical amplifiers, suitable for present broadband optical communication systems. Abstract : This work is focused on development of Erbium (Er) doped nano‐engineered scandium‐phospho‐yttria‐alumina‐silica (SPYAS) glass‐based optical fiber through a suitable thermal annealing of pristine preform. The results suggest that incorporation of Er into nano‐phase‐separated crystalline scandium‐yttria rich particles offer a flat‐gain spectrum about 38.675 dB with variations of less than ±0.70 dB over the whole range spanning 1530–1590 nm to be useful in broadband optical fiber communication systems.